Upaya Guru dalam Mengatasi Siswa yang Berkesulitan Belajar (Calistung) Baca, Tulis dan Hitung) di Kelas Rendah SDIT Bunayya - Suhirman, Defitriana Pramesti; Yeni, Putri; Zuliani, Rizki (Lembaga Yasin AlSys, 2023)
The teacher's efforts in overcoming students who have difficulty learning CALISTUNG (Read, Write, Count) in low grades at SDIT Bunayya, the results of direct observation show that some students in grades 1, 2 and 3 still have difficulty learning calistung, in low grade students it is an obstacle to the cycle. study activities. The various difficulties in learning calistung experienced in early childhood are: lack of order or not being able to focus on learning, children having difficulty understanding what is conveyed by the teacher and difficult to capture or absorb in the child's mind when counting, not yet familiar with the concept of subtraction, and not yet fluent when repeat letters a-z. In overcoming difficulties in learning, educators use interesting learning methods and media so that children become enthusiastic about learning and make it easier for students to learn CALISTUNG. Based on this, the researcher decided in this study to choose the title